Decentralization in the Middle East and North Africa Informal Politics, Subnational Governance, and the Periphery - Demmelhuber, Thomas; Sturm, Roland (Nahoststudien. Middle Eastern Studies, 2021)
This book investigates political, economic and social links between top-down decentralisation strategies and neopatrimonial elite networks in the Middle East and North Africa (MENA). Over ten years since 2011, several MENA regimes have initiated decentralisation processes, but empirical observations suggest a gap between the formal layout and the outcome of decentralisation. The authors identify neopatrimonial networks as an explanatory factor in this respect. A comparative study of Jordan, Morocco, Tunisia and Egypt (1) looks at decentralisation from the perspective of the periphery, (2) examines decentralisation within neopatrimonial contexts, (3) includes fiscal policy and informal financial flows, and (4) analyses the international donor perspective. With contributions by Sylvia I. Bergh, Miriam Bohn, Thomas Demmelhuber, Roland Sturm and Erik Vollmann.